Implikasi Hukum Atas Kenaikan PPN pada Barang Mewah - Ajeng Hijriatul Aulia; Risna Wendy Wiraganti; Aldo Yanuarto; Aji Santoso; Ali Murtadho Emzaed (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This study aims to analyze the legal implications of the luxury goods Value Added Tax (VAT) increase policy in Indonesia, which will take effect in January 2025. This policy is based on Law Number 7 of 2021 on the Harmonization of Tax Regulations and its derivative regulations, with the objective of increasing state revenue and reducing the consumption of luxury goods, which is often associated with economic inequality. This research employs a normative method with a literature study approach, analyzing tax regulations, academic journals, and relevant literature. The findings indicate that while this policy may enhance tax revenue and reduce economic disparity, its implementation faces challenges related to legal certainty, tax compliance, and its impact on consumer purchasing power and investment in the luxury goods sector. Additionally, the potential rise in tax disputes due to differing interpretations of luxury goods classification is a major concern. Therefore, clear regulations, a more transparent tax administration mechanism, and economic impact mitigation strategies are necessary to ensure the effectiveness and fairness of this policy implementation.This study aims to analyze the legal implications of the luxury goods Value Added Tax (VAT) increase policy in Indonesia, which will take effect in January 2025. This policy is based on Law Number 7 of 2021 on the Harmonization of Tax Regulations and its derivative regulations, with the objective of increasing state revenue and reducing the consumption of luxury goods, which is often associated with economic inequality. This research employs a normative method with a literature study approach, analyzing tax regulations, academic journals, and relevant literature. The findings indicate that while this policy may enhance tax revenue and reduce economic disparity, its implementation faces challenges related to legal certainty, tax compliance, and its impact on consumer purchasing power and investment in the luxury goods sector. Additionally, the potential rise in tax disputes due to differing interpretations of luxury goods classification is a major concern. Therefore, clear regulations, a more transparent tax administration mechanism, and economic impact mitigation strategies are necessary to ensure the effectiveness and fairness of this policy implementation.